Commercial scale production of RvD4 opens the resolving door to new research. Issue 6 (30th March 2018) - Edin, Matthew L.; Zeldin, Darryl C.
Abstract : Treatment with exogenous RvD4 reveals pro‐resolving actions and suggests future therapies for treatment of acute inflammatory diseases.